Fístulas carótido-cavernosas : resultados clínico y angiográfico de los pacientes tratados por el Grupo de Neurorradiología del Hospital Universitario San Vicente de Paúl, 1995-2007, Medellín, Colombia (2011)
ABSTRACT: Carotid-cavernous fistulae are frequently found in Medellín, Colombia and their surgical treatment associates with a high rate of complications due to the peculiarities of this anatomic zone. Endovascular therapy has become the first option in patients with these lesions.Objective: to describe the main demographic, clinical and angiographic features of a group of patients with carotid-cavernous fistulae, the therapeutic approach used in them, and the results obtained from the clinical and angiographic standpoints. Patients and methods: We reviewed the clinical charts of 51 patients treated by the Neuro-radiology Group at Hospital Universitario San Vicente de Paúl, in Medellín, Colombia, between 1995 and 2007. The following information was taken into account: demographic variables, etiology, initial and final clinical situation, therapeutic procedures, and angiographic results. Results: A total of 51 patients were found, three of which had bilateral lesions. Two patients had spontaneous resolution of their fistulae and in one more it resolved with carotid massage. Endovascular treatment was therefore carried out in only 48 patients. Average age was 35 years, and 74.5% of the patients were males. Fistulae were traumatic in 47 patients (92.2%) and spontaneous in four (7.8%). Out of the 47 traumatic fistulae, 33 (70.2%) were due to closed cranio-encephalic trauma. In 12 they were produced by firearm wounds and in two they were due to wounds with sharp instruments. In decreasing order of frequency clinical manifestations were: chemosis, proptosis, murmur, pain, decreased visual acuity and intracranial bleeding. Concerning the type of fistula (Barrow classification), they were type A in 86.0%, type B in 9.8%, type C in 1.9% and type D in 1.9%. In 32 patients (62.7%) carotid artery permeability was restored while in 19 (37.3%) occlusion was necessary. The most frequently used endovascular procedure was the balloon (34 cases) both for occlusion of the fistulous site and to carry out the trapping. Coils were used in 14 patients, stents in three and NCBA (N-butylcyanoacrylate) in four. More than one procedure was carried out in several patients. Arterial access was used in 44 cases (91.7%) and venous access in the remaining four (8.3%). Direct access by ophthalmic artery catheterization was used in two cases. Occlusion was achieved in 48 fistulae (94.1%) and a decrease in the flow in three (5.9%). Clinical follow-up, with a median of two months, revealed that 46 patients (90.2%) had complete resolution of their symptoms, four had partial resolution and one had worsening. Conclusion: This series, the largest so far published in Colombia on this subject, demonstrates the clinical and angiographic effectiveness of endovascular treatment of patients with carotid-cavernous fistulae.